Development of Entrepreneurship Curriculum in the Context of Increasing Entrepreneurial Attitudes of Junior High School Students - Siskandar Siskandar; Akhmad Shunhaji; Basrowi Basrowi (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aimed to look at the role of innovation capacity in mediating the link between the entrepreneurial and independent curriculums on entrepreneurial attitudes. In this study, this hypothesis was evaluated quantitatively. The respondents completed a questionnaire as the research instrument. Junior high school students from Serang City, Banten, Indonesia, participated in this study. 215 individuals were chosen for this study using purposive sampling, and data were analyzed using a structural equation model (SEM). Based on the path coefficient, there is a significant influence between entrepreneurship curriculum and innovation ability of 0.222 with a P-Value of 0.002 0.05. There is a considerable influence between independent curriculum on innovation ability is 0.341 with a P-Value of 0.000 0.05. A considerable influence between entrepreneurship curriculum and entrepreneurial attitude is 0.700 with a P-Value of 0.000 0.05. Independent curriculum has a significant influence on the entrepreneurial attitude of 0.128 and P-Value of 0.021 0.05. There is a considerable influence of innovation ability on the entrepreneurial attitude of 0.169 and P-Value of 0.000 0.05. The mediation test indicates that innovation capacity positively influences entrepreneurship curriculum and entrepreneurial mindset at a significant level of 5%, with P values of 2.192, which is greater than 1.96. Moreover, the capacity for innovation can act as a mediator between an autonomous curriculum and an entrepreneurial mindset, as indicated by P Values 1.96.